Phytochemical analysis and antioxidant activity of Azadirachta indica A. Juss from the Republic of Chad: in vitro and in silico studies - Brahim Mahamat Ousman; Asraoui Fadoua; Farihi Ayoub; Bouhrim Mohamed; Boussaoudi Ibtissam; El Ismaili Soumaya; Herqash Rashed N.; Shahat Abdelaaty A.; Otchom Brahim Boy; Saoud Younes (Open Chemistry)
Azadirachta indica, commonly known as neem or Mim in Chad, is recognized for its significant biological activities and is used for medicinal purposes. This study quantifies phenolic content, analyzes chemical composition via high-performance liquid chromatography–mass spectrometry, and evaluates the antioxidant activity of Mim leaf extracts with ethanol (ELE) and water (WLE). The analysis identified bioactive compounds with strong radical scavenging activity and conducted in silico studies by molecular docking with AutoDock Tools. Crystal structures were sourced from the Protein Data Bank, and the Swiss absorption, distribution, metabolism, and excretion platform analyzed the pharmacokinetic properties. Results indicated that WLE had a higher phenolic content (264.7 ± 0.03 µg gallic acid equivalent [GAE]/mg) compared to ELE (135.3 ± 0.05 µg GAE/mg). Flavonoid content was greater in ELE (138.33 ± 0.002 µg catechin equivalent [CE]/mg) than in WLE (83.38 ± 0.002 µg CE/mg). Major compounds identified through high-performance liquid chromatography coupled to mass spectrometry included diethyl phthalate in ELE (92.31%) and butylated hydroxytoluene (BHT) in WLE (28.12%). Antioxidant activities measured by 2,2-di-phenyl-1-picrylhydrazyl, 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid), and ferric-reducing power assays showed promising results for both extracts. BHT demonstrated a better affinity for glutathione reductase and lipoxygenases, while vanillin showed a strong affinity for cyclooxygenase. Most compounds exhibited high intestinal absorption and are not P-glycoprotein substrates, indicating potential for oral medication. Finally, Mim extracts contain diverse compounds that contribute to their notable antioxidant activity.